Deterrence-based trust in bargaining: Introducing a new experimental paradigm. Issue 1 (2nd January 2017) - van Dijk, Eric; Makagonova, Varia; de Kwaadsteniet, Erik W.; Schutter, Manon
ABSTRACT: Trust, especially in the initial stages of trust building, is often assumed to be the result of deterrence-based trust. While theorising acknowledges its importance, research on deterrence-based trust has been scarce. To facilitate the investigation of the concept, we designed new versions of the trust game in which we studied both trust (Experiment 1) and trustworthiness (Experiment 2). To better model deterrence-based trust we extended a trust game with an additional phase where trustors could accept or reject the trustee's distribution. We varied consequences of the rejection option as a delta bargaining game, thereby manipulating the potential for deterrence. The results showed that trustors were highly responsive to the possibility to reject the trustee's distribution. Trustees, however, seemed largely unaffected and were generally highly trustworthy. Together these findings show how trust games can meaningfully be extended to assess the effect of deterrence-based trust in bargaining.